High level of vaccination and protection against hepatitis B with low rate of HCV infection markers among hospital health care personnel in north of Iran: a cross-sectional study - Saffar Hiva; Khoshayand Negar; Parsaei Mohammad-Reza; Ghorbani Gholam-Reza; Aarabi Mohsen; Nadi Ghara Ali-Asghar; Saffar Mohammed-Jafar (BMC, 2020)
Abstract Background hepatitis B virus (HBV) and C virus (HCV) are among the leading causes of mortality worldwide. Health care personnel (HCP) are subjected to increased risk of these infections. Therefore, HBV vaccination and post-vaccination serologic testing (PVST) are recommended for them. Our objectives in this study were investigate how well the vaccination guidelines for hospital HCPs were implemented. Moreover, the prevalence rates of HBV and HCV infections were calculated. To determine the presence of immunological memory, vaccinated personnel negative to antibody against HB surface antigen with one dose of HB vaccine were boosted. Methods From 1 July to 30 November 2017, a cross-sectional study among HCPs working in public hospitals were conducted. All HCPs from various professional categories potentially at risk of exposure to contaminated sources were included. The information was gathered via interview and self-administered questionnaire. The questions were focused on the demographic characteristics, HB vaccination and immunity status and time elapsed since initial vaccination series, and frequency of needelstick injuries during the past 12 months of their work. Moreover, the prevalence rate of HBV and HCV infections were calculated. To determine the presence of immunological memory, subjects negative to HBV seromarkers received a booster dose of the vaccine. Results A total of 186 out of 766 participants were male and nurses comprised 71% of personnel. Although all HCP were vaccinated, 84% of them completed the course and less than 5% of them received PVST. According to the results, 0.78, 4.6, and 83% were serologically positive to HBV surface antigen, antibodies against HBV core, and S antigens, respectively. Approximately, 91% of seronegative participants responded to a booster dose and only 0.91% of the personnel was anti-HCV positive. Conclusion Most HCP received full HBV vaccination course. Although a minority did PVST, the HBV vaccine-induced long-term protection and HB vaccine booster were not required. Therefore, policies should be made to increase the rate PVST after immunization. According to the results, the HCV infection rate was low and thus pre-recruitment screening was not necessary.